2002
DOI: 10.1002/1099-0690(200202)2002:4<675::aid-ejoc675>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Procedure for the Preparation of 1-(Diisopropylamino)phospholes − Application to the Synthesis of New 2,2′-Biphosphole Disulfides

Abstract: A convenient one-pot procedure for the preparation of 1-(diisopropylamino)phospholes has been developed. These phospholes have been used in a multistep procedure for synthesizing two new 2,2Ј-biphosphole disulfide compounds. The structures and stereochemistry of these compounds have been studied by X-ray diffraction analysis and by molecular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…The usual P-substituents are alkyl or aryl groups, but it has now been shown that a (di-isopropyl)amino substituent can be present provided the dehydrohalogenation is performed with metallic amides such as lithium hexamethyldisilazane (LiHMDS) rather than the usual amine bases [24]. In this new case, the requisite chlorophospholenium chloride 41 was obtained by using the aminophosphenium ion 4 0 as the dienophile in the cycloaddition reaction.…”
Section: Thfmentioning
confidence: 99%
See 4 more Smart Citations
“…The usual P-substituents are alkyl or aryl groups, but it has now been shown that a (di-isopropyl)amino substituent can be present provided the dehydrohalogenation is performed with metallic amides such as lithium hexamethyldisilazane (LiHMDS) rather than the usual amine bases [24]. In this new case, the requisite chlorophospholenium chloride 41 was obtained by using the aminophosphenium ion 4 0 as the dienophile in the cycloaddition reaction.…”
Section: Thfmentioning
confidence: 99%
“…Finally, oxides of 1-dimethyl-and 1-diethylamino phospholes are known to dimerize on formation [86] but it has recently been found [24] that the larger 1-diisopropylamino group provides sufficient steric hindrance as to make phospholes 210 ( 46.90) and 211 ( 42.98) stable at 40° C for 48 hr. or at 110° C in toluene for 4 hr.…”
Section: Phospholes With Coordination Number 4 2h-and 3h-phospholesmentioning
confidence: 99%
See 3 more Smart Citations